Social Justice and Community Development: A Multilevel Community Engagement Model to Effectively Work with Families Living in Culturally-Diverse Communities in Pakistan - Raza, Hassan (ASEAN Journal of Community Engagement, 2021)
The current paper introduces the Multilevel Community Engagement Model (MCEM) to help development agencies effectively work with families living in diverse communities in Pakistan. This model is grounded in family systems theory, participatory action research (PAR), and ecological systems theory. It is also informed by three empirical studies and the author’s reflections of his direct observations and experiences based on his work with development agencies. The MCEM uncovers important insights about the complex, dynamic, and reciprocal interactions among different groups of stakeholders at three different engagement levels (i.e., proximal, influential, and holistic). MCEM emphasizes a strong collaboration, effective coordination, and open communication among stakeholders within and between these levels. Development agencies can use and apply MCEM, which may help them adequately understand the needs of families living in diverse communities and address those needs in socially just manners. Additionally, MCEM honors community voice and encourages local knowledge, which may magnify the efforts of stakeholders’ groups who are involved in the community development process and situated within/between three different engagement levels and ensure the successful sustainability of development projects in Pakistan. Although, this model is grounded in research, which was carried out in Pakistan, it is intended to be adapted such that it can be transformed and applied in other countries/societies/cultures. The implications and limitations of MCEM are discussed.